Dinoflagellates: ecological approaches and spatial distributions in Malaysia waters - Hamdan, Nurul Ashima; Abu Hassan, Muhamad Shafiq; Mohammad Noor, Normawaty; Abd Hamid, Shafida; Muhamad Bunnori, Noraslinda (Omics International, 2017)
Dinoflagellates are microscopic planktonic organisms that lead up the food chain in aquatic ecosystems. The naturally occurring phenomenon of Dinoflagellates blooming at the water surface brings detrimental effects to the economy as well as the environmental health of the affected ecosystem. Different types of dinoflagellates require different approaches in monitoring the excessive growth phenomenon. Identifying the vicinity of targeted species like environmental conditions is beneficial to overcome the blooming event. The tropical warm water of Malaysia eventually promotes the proliferation of harmful microalgae. Fish killings and human intoxication case reported in Malaysia to be precise are noteworthy effects brought by massive growth of Dinoflagellates. Shellfish poisonings are the silent killer to human as the outbreaks of harmful algae are obscured. Intoxication from Dinoflagellates may bring to death without prior notice. This paper provides information on Dinoflagellates growth mechanism and action potential induced by the toxins which are efficacious for mitigation and treatment purposes. Monitoring the pattern of blooming is a practical approach as no solid solution to the sudden outbreak has yet been clarified.